The Malaysian furniture industry: unravelling its growth and challenges to innovation - Ratnasingam, Jegatheswaran (Universiti Putra Malaysia Press, 2015)
This book provides an overview of the furniture industry in Malaysia, followed by a discussion of its industrial structure, production characteristics, product types, design attributes, key actors of the industry, incentive schemes, health and safety issues, trade scenario and a detailed economic analysis its performance and how it measures up in the wake of growing competition from other emerging furniture producing nations, especially China and Vietnam. Although the furniture manufacturing sub-sector is the star-performer within the Malaysian wood products industry, contributing almost one-third of total export earnings and total employment in the wood products industry, it is dogged by weak value-adding, design and innovative dynamisms due to the structural features of the industry. Weak investments in human capital and innovation activities are undermining its ambitions of becoming a net exporter of high value-added, branded furniture.